Mapping Quranic Exegesis in West Java: Influential Figures and Linguistic Insights - Munir, Moh. Sirojul; Anwar, Hoirul (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This article delves into an exploration of Tafsir Al-Quran works by influential scholars from the West of Java. Unlike traditional geographic delineations, this study does not restrict its focus to the administrative boundaries of West Java as a province but extends to broader regions in the western part of the island. The investigation employs a qualitative research methodology, primarily engaging in library research which involves the comprehensive collection and analysis of data from authoritative books on the subject. Moreover, the study is enriched by a manuscript study approach, where ancient and contemporary Tafsir texts authored by scholars from this region are examined in detail. Through this meticulous research, the study has uncovered numerous Tafsir works, each bearing the unique interpretative style of its author. The findings highlight the intellectual and theological contributions of these scholars, emphasizing the diversity and richness of Islamic scholarship in western Java. One of the distinctive features of these Tafsir works is their linguistic variety. The texts are found in Arabic, which is widely used in Islamic scholarly writings, as well as in Sundanese and Indonesian, which reflects the local linguistic and cultural integration into Islamic scholarship.The study not only sheds light on the specific Tafsir works and the scholars behind them but also paints a broader picture of the religious and cultural landscape in western Java. This approach provides valuable insights into how regional characteristics influence religious interpretation and contribute to the broader discourse in Islamic studies. The research is pivotal for scholars interested in regional Islamic studies, comparative religion, and the interplay between language, culture, and religious scholarship.. Contribution: This research reveals the diversity of Quranic exegesis by scholars in western Java and the influence of culture and language in regional Islamic studies.